Four Wooden New Kingdom Female Statuettes in the Egyptian Museum, Cairo - El-Tiebi, Amr (Études et Travaux, 2017)
The author analyzes four wooden female statuettes from the collection of the Egyptian Museum in Cairo. All of them represent nude females and have many features in common. They were rendered in a way that emphasized their sexuality and fertility. Due to the lack of inscriptions their dating and function could be reconstructed only on the basis of analogies.